2019
DOI: 10.1186/s13018-019-1386-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel rat model of tibial fracture for trauma researches: a combination of different types of fractures and soft tissue injuries

Abstract: BackgroundThe outcomes for open tibial fractures with severe soft tissue injury are still a great challenge for all the trauma surgeons in the treatment. However, most of the existing open tibial fracture models can only provide minimal soft tissue injury which cannot meet the requirement of severe trauma research. Our goal is to investigate a novel tibial fracture model providing different fractures combined with soft tissue injury for better application in trauma research.MethodsA total of 144 Sprague-Dawley… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…It was also reported that soft tissue trauma could delay periosteal response to healing [46,47]. The findings of this study agreed with that of Shi et al [20] where soft tissue injury persisted for seven days postoperative. Although the severity of the soft tissue damage they recorded was greater when compared to this study, the likely reason why they have severe soft tissue injury is that the fracture model they generated was the closed type.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It was also reported that soft tissue trauma could delay periosteal response to healing [46,47]. The findings of this study agreed with that of Shi et al [20] where soft tissue injury persisted for seven days postoperative. Although the severity of the soft tissue damage they recorded was greater when compared to this study, the likely reason why they have severe soft tissue injury is that the fracture model they generated was the closed type.…”
Section: Discussionsupporting
confidence: 92%
“…For example, 15%, 9% and 12% of the rats were excluded by Jackson et al [11]; Manigrasso and O'Connor, [41]; Auregan et al [15] respectively. In a recent study conducted by Shi et al [20], the complications of closed tibial fracture was categorized into type I to III, with type III having the severe localized injuries ranging from muscles avulsion, vascular rupture, ischemia of distal extremities and bonny comminution. These limitations make the techniques of these popular fracture models to be a little bit difficult to be reproducible without modifications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Injury induces an immunological response from acute tissue damage incurred during surgical procedures such as laparotomy, 31 castration, 23 or implantation of a biomaterial. Additionally, inflammation can be induced via bone fracture 40 or creation of segmental bone defects 2 …”
Section: Models Of Injurymentioning
confidence: 99%
“…IL‐1β and IL‐10 have been explored in response to tibial fractures 40 . Fractures were created in Sprague Dawley rats using an adjustable drop tower‐blade apparatus using a 3‐, 10‐, or 15‐mm buffer disc, which controlled the depth the blade penetrated the limb 40 . For all fracture groups, a 500 g blade was dropped from 50 cm.…”
Section: Models Of Injurymentioning
confidence: 99%